A Review of Picture Exchange Communication Interventions Implemented by Parents and Practitioners. Issue 3 (2nd July 2016) - Alsayedhassan, Batool; Banda, Devender R.; Griffin-Shirley, Nora
ABSTRACT: The picture exchange communication system (PECS) is widely used with individuals with Autism Spectrum Disorders (ASD) and other developmental disabilities to improve communication skills. Several studies indicate the positive outcomes of PECS on communication skills of children with ASD. We reviewed 13 studies that included training parents and practitioners to implement PECS with individuals with ASD. Results indicate that the parents and practitioners in these studies mastered the PECS stages in which they were trained and implemented the intervention. In addition, in many of the studies individuals with ASD acquired communication skills. The results are discussed and directions for future research are provided.